Visual Rhetoric of the Jewel with The Infant Jesus in the Setting of Arma Christi - Ewa Letkiewicz (Archiwa, Biblioteki i Muzea Kościelne)
Against the background of known modern jewellery, a particularly unique example is the jewel with a representation of the infant Jesus surrounded by arma Christi. It was sewn onto the ruby cloth of the image of the Mother of God in the monastery of the Pauline Fathers at Jasna Góra in Częstochowa. Expensive materials were used to make it, including gold, rubies, colourful enamel in white, green and blue. The jewel has been mentioned several times in the literature, dating to around the mid-17th century, but has not yet been subject of a study. The article attempts to decipher the iconography, symbolism, place of creation of the jewel, as well as its surprising subject matter resulting from the combination of the Infant Jesus with the tools of the Passion associated with the death of the adult Christ. Reflections on the jewel aimed to provide information about the functions and meanings attached to it, to recognize the means contained in the peculiar iconographic message, and to consider the potential effects it could have had. In connection with the unusual visual message, visual rhetoric, with its questions about the overt and covert meanings of the work, about the functions and purposes of the particular juxtaposition of the elements of the jewel, their symbolism, the references contained in them, was in the centre of attention.